1998
DOI: 10.1093/brain/121.10.2003
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus context in hemineglect

Abstract: Rightward deviation on bisection of a horizontal line is well described in patients with right brain injury and left hemineglect. Because of the observation that hemineglect patients may bisect very short lines to the left of the true midpoint (the so-called crossover effect), additional models have been proposed to incorporate this finding into existing theories of hemineglect. We investigated a line-length effect in six patients with left hemineglect. When presented with any set of lines of uniform (referenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 19 publications
2
21
0
Order By: Relevance
“…Poulton (1979Poulton ( , 1968 identified six types of "response bias" in magnitude estimation that can lower the size of the power function exponent. So far, contextual effects are the only form of response bias that has been examined in neglect (Ishiai, Koyama, et al, 2004;Ricci & Chatterjee, 2001;Marshall et al, 1998). Both Ishiai, Koyama, et al (2004) and Marshall et al (1998) explain crossover as due to exaggerated stimulus context effects in neglect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Poulton (1979Poulton ( , 1968 identified six types of "response bias" in magnitude estimation that can lower the size of the power function exponent. So far, contextual effects are the only form of response bias that has been examined in neglect (Ishiai, Koyama, et al, 2004;Ricci & Chatterjee, 2001;Marshall et al, 1998). Both Ishiai, Koyama, et al (2004) and Marshall et al (1998) explain crossover as due to exaggerated stimulus context effects in neglect.…”
Section: Discussionmentioning
confidence: 99%
“…So far, contextual effects are the only form of response bias that has been examined in neglect (Ishiai, Koyama, et al, 2004;Ricci & Chatterjee, 2001;Marshall et al, 1998). Both Ishiai, Koyama, et al (2004) and Marshall et al (1998) explain crossover as due to exaggerated stimulus context effects in neglect. In contrast, Ricci and Chatterjee (2001) found that absolute line length influences line bisection performance more than stimulus context in neglect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…McCourt and Jewell [82] found rightward errors with short lines and leftward errors with medium and long length lines. Finally, Marshall et al [78] report that the crossover eect in neglect patients occurs only when lines of heterogeneous lengths are presented within single blocks of trials, and is not found when a homogeneous block of short lines is presented. If similar context-dependent eects of line length are shown to occur with respect to pseudoneglect, this may explain some portion of the between-study variability.…”
Section: Line Lengthmentioning
confidence: 99%
“…The perceived midpoint was calculated by averaging the percent deviations from the true midpoint on a scale from Ϫ100% (left end of the line) to ϩ100% (right end of the line). 10 Letter cancellation consisted of 72 black letters in nonlinear array with 12 A's in the left and right visual fields, respectively, and 24 distractive elements in each field. The patient was instructed to touch each letter A.…”
Section: Study Measuresmentioning
confidence: 99%